Quality Collection Analysis of Digital Library of Universitas Airlangga - Halim, Yunus Abdul (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2017)
Digital library is a library that has a collection of books in the form of digital formats and which can be accessed by computer. The digital collection is usually a collection of research, thesis, thesis, desertation and e-book. The quality of the collection is crucial to the development of digital libraries. This study uses IFLA standard (2001), where the quality of digital collections can be measured from the quality of the content, access collection and information retrieval. This study aims to analyze the quality of digital library collection of Airlangga University using quantitative discriptive method with 100 respondents. Based on the research result, it can be concluded that the quality of digital library collection of Airlangga University is very good, that is 87.32% with assessment for collection content (86.72%), access collection (93.33%) and information retrieval (81.93%). Development needs to be done to model information retrieval in order to use the weighting method and index because the method used only uses query methods without considering the users searching behavior.Â